Rancang Bangun Mesin Steam Jet Mini Portable Power Spayer - Akhmadi, Amin Nur; Fatkhurrozak, Faqih; Sanjaya, Firman Lukman (CV. IRA PUBLISHING, 2024)
This research discusses the mini portable power spayer steam jet machine by testing it with a flow meter to find out the specifications. This machine is designed to be easily moved from one place to another. This machine has a pump that can create high water pressure. This steam jet machine can be operated using a DC motor. This machine is usually built with materials that are resistant to corrosion and durable for long-term use. To create a mini portable power spayer steam jet machine that has a simple, cheap, easy to operate and maintain system, this machine must be designed so that easy to move from one place to another, both indoors and outdoors, must be able to produce water vapor at a high enough pressure to clean dirt, the design must consider safety aspects to protect users from injury or potential danger, by designing the machine mini portable power spayer pump with dimensions that match those on the market, realized with real and existing designs and products, by testing with a flow meter, the test was carried out with a spray result of 6 liters/minute according to specifications. Making a design for a mini portable power spayer steam engine pump with an inventor that is realized is the same as choosing a product on the market. The process of testing the mini portable power spayer steam machine with a flow meter measuring tool produces a water jet pressure of 6 liters/minute, when tested with a flow meter spayer gun in a straight water jet pressure position.